Effects of surface crack on the mechanical properties of Silica: A molecular dynamics simulation study. (15th February 2019) - Chowdhury, Sanjib C.; Wise, Ethan A.; Ganesh, Raja; Gillespie, John W.
Graphical abstract: Highlights: Fracture mechanisms and crack tip morphology in silica glass are studied. Simplified atomistic J-integral method is developed for fracture toughness. Surface crack significantly affects the fiber strength. MD prediction projects about 35 nm surface crack could reduce strength to 3.5 GPa. MD strength prediction is in good agreement with the theoretical prediction. Abstract: In this paper, fracture mechanism and the effects of surface crack on the mechanical properties (modulus and strength) of silica glass are studied through reactive all-atom molecular dynamics (MD) simulations. Tapered surface cracks of different length ranging from 0.25 to 10.0 nm are created by deleting atoms to study the crack length effects. Interatomic interactions are modeled with state-of-the-art reactive force field ReaxFF and fracture energy release rate is determined from discretized atomistic J-integral approach. Simulation results indicate that surface cracks have no effect on fiber modulus, however, fiber strength is significantly affected by surface crack. With the increase in crack length, strength decreases and MD predicted strength-crack length response is in good agreement with theoretical prediction. MD simulations project that about 35 nm size crack could reduce glass fiber strength to 3.5 GPa, which is experimentally observed fiber mean strength. MD simulations show that there is no inelastic process zone with cavities in front of the crack tip. Fracture mode is brittle type where crack growth initiates through Si-O bond breakage and it propagates through sequential bond ruptures.